The MYC mRNA 3′‐UTR couples RNA polymerase II function to glutamine and ribonucleotide levels. (13th April 2017) - Dejure, Francesca R; Royla, Nadine; Herold, Steffi; Kalb, Jacqueline; Walz, Susanne; Ade, Carsten P; Mastrobuoni, Guido; Vanselow, Jens T; Schlosser, Andreas; Wolf, Elmar; Kempa, Stefan; Eilers, Martin
Abstract: Deregulated expression of MYC enhances glutamine utilization and renders cell survival dependent on glutamine, inducing "glutamine addiction". Surprisingly, colon cancer cells that express high levels of MYC due to WNT pathway mutations are not glutamine‐addicted but undergo a reversible cell cycle arrest upon glutamine deprivation. We show here that glutamine deprivation suppresses translation of endogenous MYC via the 3′‐UTR of the MYC mRNA, enabling escape from apoptosis. This regulation is mediated by glutamine‐dependent changes in adenosine‐nucleotide levels. Glutamine deprivation causes a global reduction in promoter association of RNA polymerase II (RNAPII) and slows transcriptional elongation. While activation of MYC restores binding of MYC and RNAPII function on most promoters, restoration of elongation is imperfect and activation of MYC in the absence of glutamine causes stalling of RNAPII on multiple genes, correlating with R‐loop formation. Stalling of RNAPII and R‐loop formation can cause DNA damage, arguing that the MYC 3′‐UTR is critical for maintaining genome stability when ribonucleotide levels are low. Synopsis: Glutamine and its metabolite adenosine control translation of MYC via the 3′‐UTR, linking RNA polymerase II (RNAPII) function to nucleotide availability. Bypassing this control induces stalling of RNAPII and R‐loop formation. Glutamine deprivation inhibits translation of MYC via the 3′‐UTR. The 3′‐UTR allows MYC‐driven tumour cells to escape from glutamine addiction. Adenosine is the critical downstream effector of glutamine. Control of MYC levels by adenosine links global RNAPII function to nucleoside availability. Abstract : Glutamine and its metabolite adenosine control translation of MYC via the 3′‐UTR, linking RNA polymerase II (RNAPII) function to nucleotide availability. Bypassing this control induces stalling of RNAPII and R‐loop formation.